THE BENEFITS OF TRADITIONAL GAMES ON EARLY CHILDHOOD GROSS MOTOR DEVELOPMENT IN THE DIGITAL ERA - eka (Awladuna: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to optimize the gross motor development of early childhood through the implementation of traditional games based on outdoor learning in the digital era. A qualitative approach with a case study design was employed in Kelompok Bermain Tunas Harapan. The research subjects consisted of children aged 4–6 years, teachers, and parents selected purposively. Data were collected through observation, in-depth interviews, documentation, and field notes, and were analyzed thematically using the Miles and Huberman model. The findings reveal that traditional games such as hopscotch, jump rope, and clogs effectively enhance children’s balance, movement coordination, large muscle strength, and self-confidence. Outdoor activities also help reduce children's dependence on digital devices while promoting social interaction. Teachers and parents responded positively to this approach as it aligns with children’s developmental needs. This study concludes that traditional game-based outdoor learning is an effective, contextual, and enjoyable strategy for improving gross motor skills while preserving local cultural values.